Morphologic and systematic data of 3 digenetic trematode species occurring in nototheniid fishes in the environs of the South Shetlands (Antarctic) - Zdzitowiecki, K. (Acta Parasitologica Polonica, 1989)
Descriptions of 2 new species and additional data on a third previously known species are presented. The description of Lecithophyllum champsocephali sp. n. (= Lecitophyllum sp. Zdzitowiecki, 1987) is based on 17 specimens from Champsocephalus gunnari caught on the shelf off Elephant Island. The new species is closely related to L. anteroporum Margolis, 1958, but differs from the latter in possessing a shorter pars prostatica of the seminal duct and larger gonads. The description of Stenakron glacialis sp. n. is based on 2 specimens from Racovitzia glacialis caught on the Joinville shelf of Bransfield Strait. The new species differs from S. kerguelense Prudhoe et Bray, 1973 in the arrangement of the gonads and uterine loops containing eggs and in the larger dimensions of the eggs. Hemiurus antarcticus Reimer, 1987 is considered identical with Glomericirrus macrouri (Gaevskaya, 1975).